2015
DOI: 10.3386/w21389
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology and Patient Health: Analyzing Outcomes, Populations, and Mechanisms

Abstract: We study the effect of hospital adoption of electronic medical records (EMRs) on health outcomes, particularly patient safety indicators (PSIs). We find evidence of a positive impact of EMRs on PSIs via decision support rather than care coordination. Consistent with this mechanism, we find an EMR with decision support is more effective at reducing PSIs for less complicated cases, using several different metrics for complication. These findings indicate the negligible impacts for EMRs found by previous studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Research has found little impact on mortality among Medicare patients of both basic and advanced EMR systems (Agha, 2014; McCullough, Parente, & Town, 2013). On the contrary, Miller and Tucker (2011) find improvements in infant mortality and Freedman, Lin, and Prince (2018) find evidence of improved patient safety for some groups of patients from more advanced systems. There has been some evidence of improved efficiency such as decreased repeated testing (Lammers, Adler-Milstein, & Kocher, 2014).…”
Section: Conceptual Framework and Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Research has found little impact on mortality among Medicare patients of both basic and advanced EMR systems (Agha, 2014; McCullough, Parente, & Town, 2013). On the contrary, Miller and Tucker (2011) find improvements in infant mortality and Freedman, Lin, and Prince (2018) find evidence of improved patient safety for some groups of patients from more advanced systems. There has been some evidence of improved efficiency such as decreased repeated testing (Lammers, Adler-Milstein, & Kocher, 2014).…”
Section: Conceptual Framework and Previous Literaturementioning
confidence: 99%
“…Tracking this outcome over this time period allows us to test the first two hypotheses that nonprofits will be more likely to be early adopters of EMRs, but this gap will close after government incentives become available. We follow Dranove et al (2014), Dranove et al (2015), and Freedman et al (2018) by defining advanced EMR adoption based on hospitals that have adopted computerized physician order entry (CPOE) or physician documentation. CPOE allows physicians to directly input orders into a computer rather than writing orders by hand and transferring them to a nurse.…”
Section: Data and Summary Statisticsmentioning
confidence: 99%
“…Starting more recently, most hospitals in the U.S. have adopted electronic medical records (EMRs), spurred in part by the HITECH Act of 2009. EMRs facilitate patient quality and safety (Parente and McCullough, 2009;Miller and Tucker, 2011;McCullough et al, 2016;Freedman et al, 2018), improve productivity (Lee et al, 2013), and can reduce costs (Dranove et al, 2014). Yet, a fundamental reason why hospitals adopt EMRs is to optimize reimbursements.…”
Section: Introductionmentioning
confidence: 99%
“…A growing literature explores the determinants of EMR adoption (Dranove et al 2015b) and the effects of EMR adoption on outcomes like cost and quality (e.g. Ahga 2014, McCullough et al 2013, Miller and Tucker 2011, Freedman et al 2015, Dranove et al 2015a).…”
Section: Introductionmentioning
confidence: 99%